(untitled) (Business Vision, 2019)
This article is framed in an investigation project called "Dynamic of agribusiness exportations sector and its incidence in sustainable rural development in Nariño"™s department between the periods of 2010 " 2018", is looking to contribute with mechanisms that allow to fortify and to encourage agriculture and agribusiness exportations with a sustainable development. Exportable offer characterization of agriculture and agribusiness sector between the periods of 2010 " 2018 allows to identify and visualize export business contributions, as well as the punctual identification of productive and competitive capacities of the department of Nariño. With the objective to define agriculture and agribusiness exportable offer, was made an analysis and revision of secondary information with statistics presents in the export declaration reported by the "Dirección Nacional de Aduanas e Impuestos, DIAN" ("National Customs and Taxes Directive), and the consolidation of the statistic information in relation with external trade that Legiscomex provides, in the periods between 2010 and 2018, the compiled information is processed and systematized through whit bibliographic analysis. Has been identified 31 export products were identified, in this article a description of coffee exports is made.